PERANCANGAN BUKU KATALOG BATIK LITUHDAYA INDONESIA MENGGUNAKAN TEKNIK FOTOGRAFI FASHION SEBAGAI UPAYA MENGENALKAN KEPADA MASYARAKAT SURABAYA - Bagus, Pratama Putra; Budiardjo, Hardman; cinantya, ixsora gempita (Jurnal Art Nouveau, 2017)
Batik is currently almost alienated and less desirable by the early adult because of the many fashion products that appear and with the current model. This is due to a lack of interest response to appreciate and preserve the original cultural heritage of Indonesia. Batik is one of the heritages that must be preserved, therefore the purpose of this research is to design the book catalog of Batik Lituhdaya Indonesia photography with fashion photography technique as an effort to introduce to surabaya society. Lituhdaya Indonesia is a batik fashion industry from Surabaya. In the midst of a decline in interest in batik and many fashion industries that have sprung up by offering a contemporary product, Lituhdaya Indonesia began to awaken batik fashion in early adult. From the results of data analysis, got Keyword Communication Messages